2009
DOI: 10.1016/j.envpol.2009.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and solubility of airborne metals to four plant species grown at varying distances from two heavily trafficked roads in London

Abstract: UWE makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.UWE makes no representation that the use of the materials will not infringe any patent, copyright, trademark or other property or proprietary rights.UWE accepts no liability for any infringement of intellectual property rights in any material deposited but will remove such material from public view pending investigation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 32 publications
0
16
1
Order By: Relevance
“…3). This was inconsistent with the previous studies investigating the concentrations of heavy metals in the leaves of roadside vegetables (Nabulo et al 2006), grasses (Viard et al 2004) or other landscape plants (Peachey et al 2009). The distance from road was recognized as the main factors dominating the contents of traffic-related metals in the leaves of these roadside plants.…”
Section: Spatial Variation and Influencing Factorsmentioning
confidence: 66%
“…3). This was inconsistent with the previous studies investigating the concentrations of heavy metals in the leaves of roadside vegetables (Nabulo et al 2006), grasses (Viard et al 2004) or other landscape plants (Peachey et al 2009). The distance from road was recognized as the main factors dominating the contents of traffic-related metals in the leaves of these roadside plants.…”
Section: Spatial Variation and Influencing Factorsmentioning
confidence: 66%
“…Based on dispersion simulations for elemental carbon, the distance-decay gradient was in the range of 100-400 m from the source. For ultrafine particle counts, the gradient was 100-300 m; NO 2 had gradients of 200-500 m. Also, metals (Peachey et al, 2009) and polycyclic aromatic hydrocarbons (Schnelle-Kreis et al, 1999) have shown a distance-decay gradient for roads. While this chapter was being prepared, Karner, Eisinger & Niemeier (2010) published a systematic compilation of the proximity measurements of multiple pollutants classified by category, which is a useful addition to this discussion.…”
Section: Rationalementioning
confidence: 99%
“…Size distribution, chemical composition and source of PM on the leaf surfaces have been examined in various environments (Freer-Smith et al, 1997;Wang et al, 2006). The observed values changed obviously with distance from a road and the height of the samples due to different concentrations of PM (Peachey et al, 2009;Sternberg et al, 2010). However, an understanding of the effect of rainfall on the accumulation of PM on the leaf surfaces in a native environment with extremely high PM concentration is not sufficient.…”
mentioning
confidence: 95%
“…The capacity of plants to accumulate PM indicates considerable species-specific differences that depend mainly on the properties of the leaf surfaces. In addition, this capacity is influenced by other factors such as branch and foliage configurations, PM exposure level and meteorological conditions (Freer-Smith et al, 2005;Peachey et al, 2009;Pullman, 2009;Rodriguez-Germade et al, 2014;Saebø et al, 2012). Leaf surfaces are composed of cuticles and superimposed epicuticular waxes with a considerable ultrastructural and chemical diversity .…”
mentioning
confidence: 96%